Burns first aid treatment in remote Northern Australia. Issue 2 (March 2018) - Read, David J.; Tan, Swee Chin; Ward, Linda; McDermott, Kathleen
Highlights: Remote living and Indigenous Australians are less likely to receive adequate first aid. When Indigenous Australians did receive adequate first aid, it was more likely to have been applied by a health professional. There appears to be a deficiency of burns first aid knowledge in remote Australia which requires addressing in a culturally and linguistically appropriate fashion. Abstract: Background and objective: It is well demonstrated that adequate burns first aid treatment (BFAT) improves clinical outcomes for the injured but adequacy remains low in many studies. This study presents a twelve month assessment of the adequacy of burns first aid treatment for patients managed by the Burns Service, Royal Darwin Hospital (RDH). Methods: Prospective study design of all patients managed by the Burns Service, Royal Darwin Hospital. Data were collated from two sources; RDH Burns Registry, and the Burns Registry of Australia and New Zealand (BRANZ). Inclusion criterion was all patients managed by the Burns Service, Royal Darwin Hospital for the period 1 January 2014–31 December 2014. Variables collected and analysed include: demographics, burn mechanism, burn wound depth and adequacy of and circumstances around first aid. Results: Overall 310 cases were analysed. Most injuries involved adults (68%), 19% Indigenous persons and 70% of all patients had their burn injury occur in the urban region. Adequate BFAT occurred in 41% of cases. Adults, contact burns and those where the burn injury occurred in the remote regions were less likely to receive adequate BFAT. Indigenous persons were less likely to attempt any BFAT at all and when they did receive BFAT it was more likely applied by an emergency responder or health professional. Conclusion: Overall adequacy of BFAT is low in the Top End of the Northern Territory. Remote dwellers and Indigenous persons are at increased risk of not applying or receiving adequate BFAT. The poor level of adequate BFAT demonstrated in this study suggests that the Top End community particularly remote and Indigenous persons would benefit from targeted BFAT education programs that are delivered in a culturally and linguistically appropriate fashion.